Neuropsychiatric manifestations in patients with systemic lupus erythematosus: A study from Iran - Fatemeh Hajighaemi; Masoud Etemadifar; Zahra Sayed Bonakdar (Advanced Biomedical Research, 2016)
Background: Neuropsychiatric systemic lupus erythematosus (NPSLE) is a serious and well-known complication of systemic lupus erythematosus (SLE). There is limited evidence about the prevalence of NPSLE and its manifestations in Iran. The aim of this study was to study clinical and demographic characteristics of patients with NPSLE in an Iranian population. Materials and Methods: This was a cross-sectional study that was undertaken in two referral Clinics of Neurological and Rheumatological Disorders in Alzahra Hospital, Isfahan, Iran. Between March 2004 and June 2010, medical records of registered patients with SLE were examined. NPSLE was characterized using the American College of Rheumatology case definitions. Descriptive statistics and logistic regression were performed for statistical assessment. Results: Among 556 patients with SLE, 121 (21.7%) patients were diagnosed as NPSLE and enrolled in the study. Of whom, 94 patients were female (77.7%) and 27 patients were male (22.3%) with a female to male ratio of 3.48:1. The most common NPSLE manifestations were headache (38.8%), cerebrovascular disease (CVD) (38.8%) and seizure (26.4%). Thirty-nine patients have psychiatric disorders. Among them, 32 patients (26.4%) have periods of psychosis and mood disorder was found in 6 patients (5%). Conclusions: We identified NPSLE manifestations in 21.7% of patients; headache and CVD were the most frequent neurological manifestations. Continued studies into the pathogenesis of neurological involvement in patients with SLE are warranted.